Hsa_circ_0080608 Attenuates Lung Cancer Progression by Functioning as a Competitive Endogenous RNA to Regulate the miR-661/ADRA1A Pathway - Ren, Chengbo; Cui, Ling; Li, Ruibiao; Song, Xiao; Li, Jinqiu; Xi, Qiang; Zhang, Zhilin; Zhao, Lixia (Hormone and Metabolic Research, 2023)
Circular RNAs (circRNAs) participate in the progression of human cancers and have been broadly elucidated. Here, we aimed to elucidate the roles and functional mechanisms of hsa_circ_0080608 (circ_0080608) in lung cancer. Quantitative real-time PCR (qPCR) was performed to assess the mRNA expression levels of circ_0080608, miR-661, and adrenoceptor alpha 1A (ADRA1A). Western blotting was performed to measure ADRA1A protein levels. CCK-8, colony formation, and Transwell assays were performed to determine the effect of circ_0080608 on cell proliferation and migration. Animal models were used to assess how circ_0080608 influences tumor progression in vivo. The binding relationships of miR-661’s with circ_0080608 and ADRA1A was confirmed using dual-luciferase reporter and RIP assays. Circ_0080608 exhibited relatively low expression in lung cancer samples and cells. Lung cancer cells overexpressing circ_0080608 exhibited reduced migratory and proliferative abilities. Additionally, circ_0080608 binds to miR-661 and operates as a competing endogenous RNA (ceRNA) and shares a miR-661 binding site with the 3’ UTR of ADRA1A. Furthermore, circ_0080608 inversely regulates miR-661 expression, consequently restraining the aggressive behavior of lung cancer cells. Lung cancer cells overexpressing ADRA1A also exhibit repressed migratory and proliferative abilities. However, reintroduction of miR-661 led to a decline in ADRA1A expression, thereby attenuating the functional effects of ADRA1A. Circ_0080608 impedes lung cancer progression by regulating the miR-661/ADRA1A pathway. Our findings provide new insights into the progression of lung cancer.
Keywords: lung cancer; circ_0080608; miR-661; ADRA1A